SIFAT FISIS DAN MEKANIS PAPAN UNTAI BERARAH DARI BAMBU TALI ( (J.A. & J.H. Schultes) Kurz) Gigantochloa apus - I.M. Sulastiningsih; Dian Anggraini Indrawan; Jamal Balfas; Adi Santoso; Mohammad Isa Iskandar (Jurnal Penelitian Hasil Hutan, 2017)
Bamboo is potential as an alternative material to substitute wood. This paper examines the effects of using different resin contents and strand dimensions on the properties of its oriented strand board (bamboo OSB). Tali bamboo (Gigantochloa apus (J.A. & J.H. Schultes) Kurz) was used as raw material in manufacturing the bamboo OSB. Laboratory scale oriented bamboo strand boards were fabricated using each bamboo strand length (7.5, 10, and 15 cm) and glued with liquid phenol formaldehyde adhesive at various resin contents (6, 7 and 8%) of the bamboo strands dry 3 weight. Results show that the average density of fabricated bamboo OSB was 0.75 g/cm . Physical and mechanical properties of bamboo OSB were significantly affected by resin content, except the modulus of elasticity (MOE). Higher resin content gave better physical and mechanical properties of the boards. MOE of bamboo OSB was also significantly affected by the strand length. The longer strand dimension produces boards with higher MOE values. All oriented bamboo strand boards studied meet the Indonesian and Japanese Standard requirements of type 24 particleboard and also meet the British Standard requirements of both Type OSB/2 and Type OSB/3.